2001
DOI: 10.1097/00063110-200112000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mortality among patients discharged alive after out-of-hospital cardiac arrest does not differ markedly compared with that of myocardial infarct patients without out-of-hospital cardiac arrest

Abstract: The aim of our research was to study the long-term prognosis among patients discharged alive after an out-of-hospital cardiac arrest (OHCA) in comparison with patients discharged alive after acute myocardial infarction (AMI) without OHCA, and also to study the long-term influence of AMI in connection with OHCA. Our research was conducted in the municipality of Göteborg. We retrospectively studied patients discharged from hospital 1990-91 after an OHCA of cardiac aetiology and patients discharged after an AMI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…23 The mortality rate of arrest survivors in our study was comparable to that of out-of-hospital cardiac arrest patients. [24][25][26][27][28][29] In the case of out-of-hospital cardiac arrest survivors, ICD implantation is a highly effective secondary prevention strategy for this high-risk group. Our data suggest that a similar strategy may be effective for inhospital arrest survivors.…”
Section: Discussionmentioning
confidence: 99%
“…23 The mortality rate of arrest survivors in our study was comparable to that of out-of-hospital cardiac arrest patients. [24][25][26][27][28][29] In the case of out-of-hospital cardiac arrest survivors, ICD implantation is a highly effective secondary prevention strategy for this high-risk group. Our data suggest that a similar strategy may be effective for inhospital arrest survivors.…”
Section: Discussionmentioning
confidence: 99%
“…survival in 53 patients, from discharge after OHCA of "primary cardiac" aetiology, between 2002 to 2004. In comparison with the reference literature, we demonstrated that the initial numbers of patients sampled ranged from 48 to 95 patients, (4,11,16,19,20) and 139 to 680 patients. (1,2,5,7,17,(21)(22)(23) Most of these studies are however retrospective in nature with data obtained from central registers.…”
Section: Causes Of Deathmentioning
confidence: 74%
“…consider it important, for the accuracy of clinical status of the patient, to evaluate the physician's long-term contact with the patient from the institution of CPR in the field to outpatient follow-up. Geographically, long-term studies include localities mainly in the United States of America and Europe (Denmark, Sweden, Norway, Estonia, the Netherlands, Scotland and Northern Ireland) (3)(4)(5)9,11,(16)(17)(18)(19). Data for our study were obtained from the region of East Bohemia in the Czech Republic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations